Multiple lesions in cerebral white matter in two young adults with thoracic extramedullary tumours. Issue 3 (March 1992) - Salvi, F; Mascalchi, M; Plasmati, R; Michelucci, R; Calbucci, F; Dal Pozzo, G; Tassinari, C A
Abstract : Cranial MRI showed multiple lesions in white matter that were thought to be consistent with multiple sclerosis in two young adults presenting with symptoms of progressive myelopathy. MRI of the cervicothoracic spine around one and two years after onset showed the myelopathy to be due to mid-thoracic tumours. The tumours (an extradural meningioma and intradural neuroma) were resected with complete resolution of myelopathy in one patient but no recovery in the other. Spinal MRI (or myelography) should be performed in young patients presenting with signs of progressive myelopathy even when cranial MRI shows a picture typical of multiple sclerosis.